2007
DOI: 10.4102/ojvr.v74i1.137
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the toxicity of an aqueous extract of the leaves of <i>Abrus precatorius</i> in rats

Abstract: The toxic effects of an aqueous extract of Abrus precatorius were studied in 20 male white rats over a period of 18 days. The rats were divided into four groups of five rats per group. Those in Group A served as controls while the rats in Groups B, C and D were dosed per os with 400 mg/kg, 800 mg/kg and 1 600 mg/kg of the extract, respectively. Blood samples were collected for haematological and biochemical analysis and specimens of the liver, kidney and testes were taken for histopathological studies. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 8 publications
2
31
0
Order By: Relevance
“…Human to hamster, rat, guinea-pig, rabbit, monkey, cat, baboon, ferret, Table 3. At dose range between 400 and 1600 mg/kg body weight reported by Adedapo et al (3), there was decreased RBC, PCV and Hb which were increased in mice (40,44). White blood cells and lymphocytes were decreased in rat (3) ( Table 4).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Human to hamster, rat, guinea-pig, rabbit, monkey, cat, baboon, ferret, Table 3. At dose range between 400 and 1600 mg/kg body weight reported by Adedapo et al (3), there was decreased RBC, PCV and Hb which were increased in mice (40,44). White blood cells and lymphocytes were decreased in rat (3) ( Table 4).…”
Section: Resultsmentioning
confidence: 87%
“…White blood cells and lymphocytes were decreased in rat (3) ( Table 4). Alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, protein, albumin, globulin, albumin/globulin ratio were reported to have increased in rats and mice (3,46). Total bilirubin, direct bilirubin and indirect bilirubin were reported to have increased in rat (3) but decreased in mice (46).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3]. Pharmacological activities such as antiinflammatory [4], antimicrobial [5], neuromuscular [6], and toxicity studies [7] are reported on leaves. It is also a major ingredient of many marketed polyhedral digestive mixtures such as Chatak ® . Leaves are foremost source of an alkaloid trigonelline [8] having diverse pharmacological activities such as hypoglycemic, hypocholesterolemic, antiseptic, antimigraine, antitumor, mutagenic, and osmoregulatory [9].…”
Section: Introductionmentioning
confidence: 99%